2009
DOI: 10.4269/ajtmh.2009.81.373
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of a Visceral Leishmaniasis Outbreak in Highland Ethiopia

Abstract: In May 2005, visceral leishmaniasis (VL) was recognized for the first time in Libo Kemken, Ethiopia, a highland region where only few cases had been reported before. We analyzed records of VL patients treated from May 25, 2005 to December 13, 2007 by the only VL treatment center in the area, maintained by Médecins Sans Frontières-Ethiopia, Operational Center Barcelona-Athens. The median age was 18 years; 77.6% were male. The overall case fatality rate was 4%, but adults 45 years or older were five times as lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 13 publications
(20 reference statements)
3
66
0
Order By: Relevance
“…In the search for factors associated with the failure of first-line treatment, the final logistic-regression model indicated that the only independent predictors were HIV infection and older age, the first reflecting, as discussed above, the profound immune imbalance determined by CD4 ϩ T-cell depletion (32). The pinpointed significance of age was in agreement with another report showing a 5-fold-greater risk of relapse in African patients older than 45 years and treated with antimonial derivatives (28). Our study documented that L-AmB, the first choice for the treatment of VL in high-income countries, was by far the most frequently drug used at all sites participating in the present retrospection, in spite of the need of "off-label" prescription.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In the search for factors associated with the failure of first-line treatment, the final logistic-regression model indicated that the only independent predictors were HIV infection and older age, the first reflecting, as discussed above, the profound immune imbalance determined by CD4 ϩ T-cell depletion (32). The pinpointed significance of age was in agreement with another report showing a 5-fold-greater risk of relapse in African patients older than 45 years and treated with antimonial derivatives (28). Our study documented that L-AmB, the first choice for the treatment of VL in high-income countries, was by far the most frequently drug used at all sites participating in the present retrospection, in spite of the need of "off-label" prescription.…”
Section: Discussionsupporting
confidence: 78%
“…Fifty-five additional centers replied they were unwilling (28) or unable (23) to participate. Twelve centers did not provide data after adhering to the survey.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, asymptomatic infections in persons 5 years of age is also consistent with active transmission, despite the low VL incidence observed after the outbreak. 6 The present study indicates the appropriateness of combining serologic analysis (DAT) and LST to obtain a consistent picture of the asymptomatic infection rate in a VL-endemic area. This work also indicates that after the 2004-2005 VL outbreak, active transmission is still occurring in the villages studied and that L. donovani transmission can potentially be established in highlands (1,800-2,000 meters above sea level) in Ethiopia, which are commonly considered free of VL.…”
Section: Discussionmentioning
confidence: 99%
“…4 Visceral leishmaniasis is fatal if left untreated, and even with treatment the case fatality rate ranges from 4% to 10%. 5,6 In stable disease-endemic areas, clinical disease appears only in a fraction of those infected, and another fraction will not develop the disease and remain asymptomatic. 7 The prevalence of asymptomatic infection is different between and within different disease-endemic countries, and the number of asymptomatic infections usually exceeds the number of symptomatic infections, although this ratio can vary from 0.4:1 to 50:1.…”
Section: Introductionmentioning
confidence: 99%
“…This has been reported previously. 19,20,[22][23][24][25] It is unclear whether this is because of factors such as increased exposure, vulnerability, or health-seeking behavior (it is possible that male patients are more likely to present to health centers for care) and how these factors vary in the different epidemiological and cultural settings. Populations were younger in Latin America than in Africa and South Asia.…”
Section: Discussionmentioning
confidence: 99%